Rituximab and Abatacept Are Effective in Differential Treatment of Interstitial Lymphocytic Lung Disease in Children With Primary Immunodeficiencies - Rodina, Yulia; Deripapa, E.; Shvets, O.; Mukhina, A.; Roppelt, A.; Yuhacheva, D.; Laberko, A.; Burlakov, V.; Abramov, D.; Tereshchenko, G.; Novichkova, G.; Shcherbina, Anna (Frontiers in Immunology, 2021)
Background Interstitial lymphocytic lung disease (ILLD), a recently recognized complication of primary immunodeficiencies (PID), is caused by immune dysregulation, abnormal bronchus-associated lymphoid tissue (BALT) hyperplasia, with subsequent progressive loss of pulmonary function. Various modes of standard immunosuppressive therapy for ILLD have been shown as only partially effective. Objectives To retrospectively evaluate the safety and efficacy of abatacept or rituximab in treatment of ILLD in children with PID. Methods 29 children (median age 11 years) with various forms of PID received one of the two therapy regimens predominantly based on the lesions’ immunohistopathology: children with prevalent B-cell lung infiltration received rituximab (n = 16), and those with predominantly T-cell infiltration received abatacept (n = 17). Clinical and radiological symptoms were assessed using a severity scale developed for the study. Results The targeted therapy with abatacept (A) or rituximab (R) enabled long-term control of clinical (A 3.4 ± 1.3 vs. 0.6 ± 0.1; R 2.8 ± 1 vs. 0.7 ± 0.05, p < 0.01) and radiological (A 18.4 ± 3.1 vs. 6.0 ± 2.0; R 30 ± 7.1 vs. 10 ± 1.7, p < 0.01) symptoms of ILLD in both groups and significantly improved patients’ quality of life, as measured by the total scale (TS) score of 57 ± 2.1 in treatment recipients vs. 31.2 ± 1.9 before therapy (p < 0.01). Conclusions ILLD histopathology should be considered when selecting treatment. Abatacept and rituximab are effective and safe in differential treatment of ILLD in children.